The optimal degree of discretion in monetary policy - Susan Athey; Andrew Atkeson; Patrick J. Kehoe (European Central Bank (ECB), 2004)
How much discretion should the monetary authority have in setting its policy? This question is analyzed in an economy with an agreed-upon social welfare function that depends on the randomly fluctuating state of the economy. The monetary authority has private information about that state. In the model, well-designed rules trade off society's desire to give the monetary authority discretion to react to its private information against society's need to guard against the time inconsistency problem arising from the temptation to stimulate the economy with unexpected inflation. Although this dynamic mechanism design problem seems complex, society can implement the optimal policy simply by legislating an inflation cap that specifies the highest allowable inflation rate. The more severe the time inconsistency problem, the more tightly the cap constrains policy and the smaller is the degree of discretion. As this problem becomes sufficiently severe, the optimal degree of discretion is none.
Keywords: E5; E6; E52; E58; E61; 330; inflation caps; inflation targets; optimal monetary policy; Rules vs discretion; time inconsistency